Trust Deficit in Surgical Systems in an Urban Slum in India Under Universal Health Coverage: A Mixed Method Study - Kranti Vora; Shahin Saiyed; Dileep Mavalankar; Lyndsay S. Baines; Rahul M. Jindal; Rahul M. Jindal (Frontiers Media S.A., 2022)
Objectives: We carried out a mixed method study to understand why patients did not avail of surgical care in an urban slum in India.Methods: In our earlier study, we found that out of 10,330 people, 3.46% needed surgery; 42% did not avail of surgery (unmet needs). We conducted a follow-up study to understand reasons for not availing surgery, 141 in met needs, 91 in unmet needs. We administered 2 instruments, 16 in-depth interviews and 1 focused group discussion.Results: Responses from the 2 groups for "the Socio-culturally Competent Trust in Physician Scale for a Developing Country Setting" scale did not have significant difference except for, prescription of medicines, patients with unmet needs were less likely to agree (p = 0.076). Results between 2 groups regarding "Patient perceptions of quality" did not show significant difference except for doctors answering questions where a higher proportion of unmet need group agreed (p = 0.064). Similar observations were made in the in depth interviews and focus group.Conclusion: There is a need for understanding trust issues with health service delivery related to surgical care for marginalized populations.